2017
DOI: 10.2967/jnumed.117.199406
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a Biologic Variable in Preclinical Imaging Research: Initial Observations with 18F-FLT

Abstract: The study objective was to investigate whether sex influences 3'-deoxy-3'-F-fluorothymidine (F-FLT) uptake and tissue distribution in mouse models of cancer. F-FLT biodistribution was measured in 3 strains of male and female mice (129S6/SvEv, athymic nude, and BALB/c).F-FDG biodistribution was measured for comparison. F-FLT uptake was also measured in female 129S6/SvEv mice bearing estrogen-dependent SSM3 mouse mammary tumors, male athymic nude mice bearing androgen-dependent CWR22 prostate cancer xenografts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…We did not observe any substantial signal in tumors with 68 Ga-substance P. 18 F-FDG PET scan was also in the line with our ex vivo data and previously published imaging data, showing predominant accumulation of radioactivity in the heart, spleen, tumor and interscapular brown adipose tissue [23]. Similarly, data from 18 F-FLT PET imaging were in congruence with ex vivo results with the highest activity seen in the spleen, gastrointestinal tract, tumor, and largest bone tissue sites, such as knees, what confirms the findings published by Chan et al [30]. The data gained from PET acquisitions were also used for the uptake quantification of the tracers in tumor and brain regions by calculation of standardized uptake values (SUV).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not observe any substantial signal in tumors with 68 Ga-substance P. 18 F-FDG PET scan was also in the line with our ex vivo data and previously published imaging data, showing predominant accumulation of radioactivity in the heart, spleen, tumor and interscapular brown adipose tissue [23]. Similarly, data from 18 F-FLT PET imaging were in congruence with ex vivo results with the highest activity seen in the spleen, gastrointestinal tract, tumor, and largest bone tissue sites, such as knees, what confirms the findings published by Chan et al [30]. The data gained from PET acquisitions were also used for the uptake quantification of the tracers in tumor and brain regions by calculation of standardized uptake values (SUV).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, 18 F-FLT exhibited relatively uniform accumulation across all studied organs (4–6% ID/g). Nevertheless, this was expected according to the literature [30]. The decrease of tracer uptake between 30 and 90 min post injection was apparent, but it was not the case for spleen, intestine, bone and tumor, On the contrary to 68 Ga-tracers, 18 F-tracers had tumor to blood ratio of 2.0.…”
Section: Discussionmentioning
confidence: 58%
“…For instance, Okita et al (7) have shown that smoking cigarettes affects the D2 receptor to different degrees in men and women. Animal experiments have demonstrated sex effects on receptor uptake of radioactive ligands (8). One pre-clinical study has shown sex effects on the upregulation of D2 receptors after treatment with haloperidol or clozapine (9).…”
Section: Neurotransmitter Receptors and Sexmentioning
confidence: 99%
“… 3,4 While we see selective uptake in paired TMPK-high and TMPK-low cells, the evidence from this work suggests that [ 18 F]SqFLT behaves more in line with an antagonist than a substrate. 26–28 Future studies of [ 18 F]SqFLT or analogues should consider how the sex of a mouse cancer model influences tumour uptake and tissue biodistribution, as previously reported for [ 18 F]FLT; 29 given the poor in vivo performance of [ 18 F]SqFLT, this was not further considered as part of this study. Incubation of [ 18 F]SqFLT with human liver microsomes (HLM) showed no metabolism over 60 min.…”
Section: Resultsmentioning
confidence: 99%